Pemberian Rasywah Untuk Mendapatkan dan Mempertahankan Hak dalam Kajian Filsafat Hukum Islam - Syafriadi B; Busyro Busyro; Irvan Refliandi; Erizal Erizal (Hikmah, 2023)
Giving rashwah has been agreed upon that it is forbidden by Muslim scholars based on the hadith of the Prophet. However, in certain cases related to defending rights, there is a dilemma between giving rashwah and not giving. When using rashwah, there are hadiths that prohibit it, but when rashwah is not given, rights that should belong to someone will be lost. This study aims to examine the views of Islamic legal philosophy towards giving rashwah to defend one's rights. This study used the library research method with a qualitative approach. Data was collected by reading various related references and then making comparisons. Data analysis was carried out using comparative and descriptive methods. The results of the study show that a person must defend his right to guarantee the maintenance of one of al-dharuriyah al-khams, such as property, as an objective of Islamic law even though in general it is contrary to standard legal principles to realize the achievement of maqāsid syar'iyyah namely the realization of maṣlahah in the form of hifzhul mal (protection of assets) so that the implication is that rights which are part of assets can be maintained and sustained.